Identification and characterization of novel rapidly mutating Y‐chromosomal short tandem repeat markers. Issue 9 (11th July 2020) - Ralf, Arwin; Lubach, Delano; Kousouri, Nefeli; Winkler, Christian; Schulz, Iris; Roewer, Lutz; Purps, Josephine; Lessig, Rüdiger; Krajewski, Pawel; Ploski, Rafal; Dobosz, Tadeusz; Henke, Lotte; et al.
Abstract: Short tandem repeat polymorphisms on the male‐specific part of the human Y‐chromosome (Y‐STRs) are valuable tools in many areas of human genetics. Although their paternal inheritance and moderate mutation rate ( 10 −3 mutations per marker per meiosis) allow detecting paternal relationships, they typically fail to separate male relatives. Previously, we identified 13 Y‐STR markers with untypically high mutation rates (>10 −2 ), termed rapidly mutating (RM) Y‐STRs, and showed that they improved male relative differentiation over standard Y‐STRs. By applying a newly developed in silico search approach to the Y‐chromosome reference sequence, we identified 27 novel RM Y‐STR candidates. Genotyping them in 1, 616 DNA‐confirmed father–son pairs for mutation rate estimation empirically highlighted 12 novel RM Y‐STRs. Their capacity to differentiate males related by 1, 2, and 3 meioses was 27%, 47%, and 61%, respectively, while for all 25 currently known RM Y‐STRs, it was 44%, 69%, and 83%. Of the 647 Y‐STR mutations observed in total, almost all were single repeat changes, repeat gains, and losses were well balanced; allele length and fathers' age were positively correlated with mutation rate. We expect these new RM Y‐STRs, together with the previously known ones, to significantly improving male relative differentiation in future human genetic applications.